Seasonal distribution of phenolics in leaves of aromatic plants (Origanum vulgare L., Mentha spicata L., Clinopodium vulgare L.) and their ecophysiological implications - Kofidis, George; Bosabalidis, Artemios M. (Biological Letters, 2013)
Seasonal distribution of phenolics was studied in leaves of 3 species of the family Lamiaceae: Origanum vulgare L., Mentha spicata L., and Clinopodium vulgare L. Phenolic compounds were identified in fresh leaves by a histochemical test and quantified morphometrically by point-counting analysis. The summer leaves (August) of O. vulgare contained the highest amounts of phenolics, as compared to M. spicata and C. vulgare. Phenolics were abundant in all leaf tissues (upper and lower epidermis, palisade and spongy parenchyma) of O. vulgare, but mainly in epidermal cells of M. spicata. In case of C. vulgare, however, phenolics were mostly present in the spongy parenchyma of the mesophyll. High amounts of phenolics in the summer leaves of these aromatic plants appeared to impart protection from harmful insects, microorganisms, and drought stress, rather than from UV-B radiation.